Synthesis of 4-aryl-2,6-dimethyl-3,5-bis-N-(aryl)-carbamoyl-1,4-dihydropyridines as novel skin protecting and anti-aging agents (Bangladesh Journal of Pharmacology, 2017)
A series of 4-aryl-2,6-dimethyl-3,5-bis-N-(aryl)-carbamoyl-1,4-dihydropyri-dines 6a-6h were prepared by using the one-pot three component synthetic method. The target compounds 6a-6h were synthesized by reacting two molar equivalents of ketone functionality and one mole of aromatic aldehydes in ammonium acetate to obtain the desired products. The structures of newly synthesized compounds were characterized by FT-IR, 1H-NMR, 13C-NMR, and elemental analysis. All the synthesized compounds were screened for their elastase inhibition and antioxidant activity. Almost all of the com-pounds 6a-h showed good to excellent activities against elastase enzyme more than the reference drug. Compounds 6d and 6b at 0.2 ± 0.0 µM and 0.2 ± 0.0 µM were found to most potent derivatives against elastase enzyme. Compound 6a exhibited prominent free radical scavenging activity. From the results of the biological activity, we infer that some derivatives can serve as lead molecules in pharmacology.Video Clip of Methodology:3 min 13 sec   Full Screen   Alternate